Female calves born resulted from an artificial inseminatioan (AI) using sexed sperm separated with egg albumin coloum - Situmorang p; Sianturi RG; Kusumaningrum DA; Ross .; Maidaswar . (Indonesian Center for Animal Research and Development (ICARD), 2013)
An efforts to alter the sex ratio of calves born could be made by separating spermatozoa bearing X and Y chromosome. The object of this study is to increase the female dairy calves born resulted from artificial insemination using the sexed sperm. There were 2 activities conducted which were 1) Spermatozoa separation based on two egg albumin column with a concentration of 10% as the upper column (UC) and 30% as the lower column (LC) and 2) AI using semen from UC. Experiment designed was completely randomized designed with three separation time (10, 20 and 30 minutes) for the treatments. Semen from UC which is expected rich in spermatozoa X, diluted in Tris Citrate extender to give a final concentration of 100 million sperm/cc and frozen to - 196°C for AI purposes. Results showed that separation of semen using egg albumin column, affects the size of head of spermatozoa. The means of length, width and area size of head spermatozoa were 8.7 µm, 4.7 µm, 35.7 µm2 and 8.4 µm, 4.6 µm, 33.7 µm2 for UC and LC respectively. The livability of sperm from UC and LC were not statistically significant different. The mean percentage of motile (%M), live sperm (%L) and intact apical ridge (%IAR) were 77.8, 85.5, 78.1 and 76.1, 83.5, 78.4 for UC and LC respectively. Separation time did not significantly affect the size of spermatozoa heads of UC semen. The mean length, width and area size of head of spermatozoa were 8.7 µm, 4.5 µm, 36.1 µm2; 8.7 µm, 4.8 µm, 36.2 µm2 and 8.5 µm, 4.7 µm, 34.8 µm2 for 10; 20 and 30 minutes respectively. From total of 160 calves born showed that the female calves born was 65%. It is concluded that AI using sexed sperm separated with egg albumin could increase the percentage of female calve born. Key Words: Egg Albumin, Column, Separation Time, Size Sperm, Female Calve